L'effectivité des décisions de la justice pénale - Viau, Louise (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
To measure how effective the decisions of criminal courts really are, the author identifies the various factors interfering with the application of judicial decisions. Are the decisions of foreign jurisdictions binding before the Canadian authorities for extradition purposes ? Moreover, within Canada, what factors might affect the execution of a jail sentence, a fine, or even the suspension of a driving permit ? It will be seen that some of the factors identified interfere only marginally with the decisions while others contribute significantly in modifying the decisions as pronounced by the criminal courts. The conclusion of this paper is that the effectiveness of criminal court decisions is quite relative. It follows that the imposition of a penalty upon those who fail to obey a civil judgment should not be considered as a means of ensuring the effectiveness of that judgment.